Entrepreneurial leadership self-efficacy. Adaptation and Validation of CESE Scale in Spain - Moriano, Juan A.; Topa, Gabriela; Molero, Fernando; Entenza, Ana M.; Lévy Mangin, Jean Pierre (Anales de Psicología / Annals of Psychology, 2012)
This study aims to adapt and validate a Spanish-language version of the Corporate Entrepreneurial Self-Efficacy (CESE) scale in a sample of more than two hundred Spanish managers and middle managers. This scale was originally developed by Ehrlich, De Noble and Singh (2005) in order to measure the skills needed for leading and managing teams and communicating with internal stakeholders to obtain support and corporate resources to develop new innovative projects. The results obtained, using Partial Least Square (PLS) technique, allow confirming that the Spanish version of CESE scale has a high reliability and validity to measure the main skills and activities necessaries to lead entrepreneurial initiatives inside the organization.